Influência da microestrutura na resistência mecânica de ligas hipereutéticas Al-Si solidificadas direcionalmente - Reyes, Rodrigo André Valenzuela (Universidade Federal de São Carlos, 2017)
The present research work deals with directional solidification (DS) of Al-15wt.% and 18wt.% Si alloys and further characterization of the related microstructures. Emphasis is given on the eutectic growth being affected not only by solidification kinetics (V-eutectic growth rate and G-thermal gradient) but also by melt superheat, which is varied in two degrees for each alloy, i.e., 6% and 23% above the liquidus temperature. The dependences of interphase spacing (X) on both solidification kinetics (fast, intermediate and slow cooling conditions) and on melt superheat during solidification of hypereutectic alloys are reported for the first time. Furthermore, functional experimental interrelations of tensile mechanical properties and interphase spacing between eutectic Si particles of both alloys evaluated are proposed. It is shown by these correlations that the tensile properties increase with the decrease in these spacings. More significant variations in properties are associated with a certain range of spacings (1.0^m < X < 2.3^m) in the case of the Al-15wt.%Si alloy. Tensile strength and elongation-to-fracture decrease with increasing alloy silicon content. The applicability of eutectic growth expressions such as X=f (V-1/2) and X=f (G-a x V-b) has been verified for the present tested alloys and experimental conditions.
Tensile properties and related microstructural aspects of hypereutectic Al-Si directionally solidified alloys
Keywords: Ligas Al-Si; Solidificação; Microestrutura; Propriedades mecânicas; Al-Si alloys; Solidification; Microstructure; Mechanical properties; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA